Automatic identification of electric loads using switching transient current signals - Thiruvaran, T.; Phung, T.; Ambikairajah, E. (IEEE, 2013)
The automatic identification of different electric loads using the current waveform at the time of switching, is analysed in this paper. The time variation of the harmonics at the time of switching is modelled using the Hidden Markov Model with Gaussian Mixture Models representing the probabilities. Short Time Fourier Transform (STFT) and Wavelet Transform (WT) based features are compared at their optimum configurations. The STFT based feature gave an accuracy of 97.9% while the WT features provided an accuracy of 93.75% in a cross fold validation experiment.
Keywords: Electric load identification; harmonic analysis